(untitled) (Research, Society and Development, 2022)
The objective was to present and discuss the actions of public institutions to control the radioactive risk arising from uranium mining, between 2008 and 2019, in the southwest of the State of Bahia, Brazil. This is a qualitative multiple case study. 141 documents produced by the institutions and 28 interviews with managers and technicians of the institutions were analyzed. They were interpreted from the CDC/USA/WHO model for the analysis of Essential Functions in Public Health, through approximations with Hermeneutics. The results revealed: 1 - situations of institutional contrasts with different views on health and the environment in the face of the problem; 2 - that there are different management models and experiences in the face of the same phenomenon; 3 - that the institutional narratives expressed consensus in terms of low capillarity and limited technical capacity of actions to control radioactive risk 4 - low qualification of health professionals and technical conditions for the prevention and control of radioactive risk; 5 - Insufficient epidemiological information on radiation risk. It is concluded that the analyzed health and environment institutions do not have the capacity to control the radioactive risk in southwest Bahia.